2013
DOI: 10.1111/jgh.12180
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of nodular gastritis in Japanese elderly

Abstract: NG in the elderly was also suggested to be a risk factor for gastric cancer as well as in the young.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 20 publications
2
9
1
Order By: Relevance
“…Gastric atrophy is rare in NG patients ; therefore, there are low levels of PG I and a decrease of the PG I/II ratio and hypergastrinemia in the serum . Our results agree with those of previous studies and, consequently, also indicated that there was no severe atrophy and hypochlorhydria in patients with NG.…”
Section: Discussionsupporting
confidence: 92%
“…Gastric atrophy is rare in NG patients ; therefore, there are low levels of PG I and a decrease of the PG I/II ratio and hypergastrinemia in the serum . Our results agree with those of previous studies and, consequently, also indicated that there was no severe atrophy and hypochlorhydria in patients with NG.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, six (5%) cases of gastric cancers, all of which were of the diffuse type, were observed in patients with NG. Previous reports indicate that NG is a risk factor for the development of diffuse‐type gastric cancer in the gastric corpus, and our results were in line with those of previous reports. NG appears to increase the risk of developing diffuse‐type cancer due to highly active gastric inflammation and lower levels of atrophy.…”
Section: Discussionsupporting
confidence: 94%
“…Observational studies of Japanese adults with NG have suggested an association with gastric cancer, particularly diffuse‐type gastric cancer . However, the biological and epidemiological associations between NG and cancer development are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognosis differs in adults with NG; some might progress to a diffuse-type gastric cancer and a few may progress to a lymphofollicular malignancy [ 9 , 10 ]. Several studies have found reductions in symptoms and in the risk of peptic ulcers and possibly gastric cancer following H. pylori eradication [ 5 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%